2021
DOI: 10.1108/raf-06-2020-0151
|View full text |Cite
|
Sign up to set email alerts
|

Forcing responsibility? Examining earnings management induced by mandatory corporate social responsibility: evidence from India

Abstract: Purpose This study aims to investigate the impact of mandatory corporate social responsibility (CSR) spending legislation on the earnings management strategies of firms. Design/methodology/approach The authors use panel data regression models to analyze the data for this study. This study covers the post-legislation period, which spans over five years from the financial year ending March 2015 to the financial year ending March 2019. Findings The results show that firms manipulate accounting measures to avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Following prior studies (for instance, Makarem and Roberts, 2020; Zang, 2012), we measure REM through abnormal discretionary expenditure ( A_DISX ) and abnormal production costs ( A_PROD ). Following prior studies (for instance, Bansal and Ali, 2021; Bansal and Kumar, 2021), we measure AEM through abnormal accruals ( A_ACC ), where A_ACC is estimated through the performance-adjusted modified Jones model (Kothari et al , 2005). Following Joo and Chamberlain (2017), we measure expense shifting by including a dummy variable – ES that takes value equals one for firms having positive unexpected core earnings ( UE_CE ), and zero otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…Following prior studies (for instance, Makarem and Roberts, 2020; Zang, 2012), we measure REM through abnormal discretionary expenditure ( A_DISX ) and abnormal production costs ( A_PROD ). Following prior studies (for instance, Bansal and Ali, 2021; Bansal and Kumar, 2021), we measure AEM through abnormal accruals ( A_ACC ), where A_ACC is estimated through the performance-adjusted modified Jones model (Kothari et al , 2005). Following Joo and Chamberlain (2017), we measure expense shifting by including a dummy variable – ES that takes value equals one for firms having positive unexpected core earnings ( UE_CE ), and zero otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome of the study contributes to the literature in both theoretical and practical spheres. First, our study enriches the literature on accounting manipulations (for instance, Achleitner et al , 2014; Bansal and Kumar, 2021; Cohen et al , 2008; Khunkaew and Qingxiang, 2019; Zang, 2012; Zhu et al , 2015) by highlighting the differential impact of downward and upward REM on stock returns. This is among the earlier attempts that considered the upward and downward forms of earnings management while examining the association between REM and stock returns.…”
Section: Introductionmentioning
confidence: 61%
“…If it exists, then how does it impact the stock returns. Following Bansal and Kumar (2021), we measure AEM through abnormal accruals (ACC), where ACC is calculated through the performance-adjusted modified Jones model (Kothari et al , 2005). The model is as follows:where ACC denotes total accruals, measured as the difference between net income and operating cash flows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results appeared in the manufacturing sector of the economy. Hassan [32] analysed the manufacturing sector using 32 manufacturing related firms from 2007 to 2011. Hassan also used the modified Jones model as proxy for the quality of table reported in the annual statement and after robust statistical tests the results indicated that levered firms have higher earnings quality and that the relationship is proportionate.…”
Section: Empirical Evidencesmentioning
confidence: 99%